Can the MMP-9/NGAL ratio be a diagnostic biomarker for the diagnosis of endometrioma in infertile patients? - Turgay, Batuhan; Özmen, Batuhan; Kılıçkıran, Harun; Şükür, Yavuz Emre; Sönmezer, Murat; Berker, Bülent; Atabekoğlu, Cem Somer; Aytaç, Ruşen (Frontiers in Endocrinology, 2025)
ObjectiveIn this study, we aimed to investigate whether serum NGAL, MMP-9 and the MMP-9/NGAL ratio, which are inflammatory markers used for the diagnosis and follow-up of some diseases, can be used as diagnostic and follow-up markers for the diagnosis of endometriomas in infertile patients.MethodsForty-five patients with unexplained infertility and 45 infertile patients with endometriomas were included in the study. Patients with endometriomas of at least 3 cm in size were included in the study. NGAL and MMP-9 levels in venous blood samples and the MMP-9/NGAL ratios of the unexplained infertility and endometrioma groups and the preoperative and postoperative results of the endometrioma group were compared.ResultsThe mean blood NGAL and MMP-9 levels in the endometrioma and unexplained groups were 22.0 ± 4.0 ng/ml and 25.4 ± 4.9 ng/ml and 43.7 ± 8.0 ng/ml and 39.3 ± 10.7 ng/ml, respectively, and all the results were statistically significant (p=0.001; p=0.012). The mean blood levels of NGAL and MMP-9 in endometriomas and the same patients at three months after surgery were 24.9 ± 4.9 ng/ml and 27.0 ± 4.9 ng/ml and 43.9 ± 7.3 ng/ml and 36.7 ± 8.7 ng/ml, respectively (p=0.179; p=0.006). The mean ratios of MMP-9/NGAL in the endometrioma, unexplained and postoperative groups were 2.0 ± 0.2, 1.5 ± 0.2 and 1.4 ± 0.2, respectively. All these results were significantly different between the endometrioma-unexplained group and the endometrioma-postoperative group (p=0.001; p=0.001). When we performed a ROC curve analysis for the presence of endometrioma, an MMP-9/NGAL ratio greater than 1.75 had 86.1% sensitivity and 84% specificity in indicating the presence of endometrioma (AUC=0.898). There was a positive correlation between the VAS score and the MMP-9/NGAL ratio.ConclusionsInterestingly, the NGAL blood NGAL level was lower in the endometrioma group than in the control group. The MMP-9/NGAL ratio can be useful in the diagnosis of endometrioma, and this ratio reflects the clinical findings of the disease.